THE ISSUE OF EXECUTION NON-CUSTODIAL PUNISHMENTS FOR MINORS - Sarvinoz Kulturaeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
in this article the author conducted the issues of the related to the effective execution non-custodial punishments. As well as, offers on improvement of the acts regulating this sphere are provided.